2011
DOI: 10.1017/s0007114511002418
|View full text |Cite
|
Sign up to set email alerts
|

Fish intake, erythrocyten-3 fatty acid status and metabolic health in Danish adolescent girls and boys

Abstract: Marine n-3 long-chain PUFA (n-3 LCPUFA) may have a beneficial effect on several aspects of the metabolic syndrome (dyslipidaemia, insulin resistance, hypertension and abdominal obesity). The metabolic syndrome is increasing in prevalence during adolescence, but only few studies have investigated the effects of n-3 LCPUFA in adolescence. The present study examines associations between fish intake (assessed by a 7 d pre-coded food diary), erythrocyte (RBC) DHA status (analysed by GC) and metabolic syndrome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
6
17
2
Order By: Relevance
“…This is in agreement with the positive association observed between breast-feeding duration and RBC DHA and EPA levels in Danish adolescents (8) . When replacing breast-feeding status by breast-feeding duration, we observed a positive and significant association with RBC n-3 PUFA but not with RBC n-6 PUFA.…”
Section: Multivariate Modelssupporting
confidence: 92%
“…This is in agreement with the positive association observed between breast-feeding duration and RBC DHA and EPA levels in Danish adolescents (8) . When replacing breast-feeding status by breast-feeding duration, we observed a positive and significant association with RBC n-3 PUFA but not with RBC n-6 PUFA.…”
Section: Multivariate Modelssupporting
confidence: 92%
“…Beneficial effects of n-3 PUFA on BP have been shown in several intervention studies investigating the effect of supplemental FA intake [4850] and in observational studies investigating dietary intake [8, 23, 5153]. While observational studies investigating the association of n-3 PUFA blood levels and BP showed beneficial effects in adults [11, 42], results in children and adolescents were not consistent and indicated unfavorable effects [24, 25, 40]. In a Danish cross-sectional study including 8–11 year old children, whole-blood EPA was associated with a 2.7 mmHg higher DBP per weight% EPA in boys but not in girls [24].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, our data point to an inverse association of DHA with SBP in thin/normal weight children at baseline though the effect estimate did not reach statistical significance. In contrast, two smaller cross-sectional studies showed that whole-blood DHA was positively associated with DBP in 8–11 year old boys [40] and that erythrocyte DHA was positively related with SBP in 17 year old adolescents [25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Nonetheless, studies that have investigated the effects of PUFA supplementation on cardiovascular risk factors and cardiovascular outcomes have yielded inconsistent results. [12][13][14] Because fatty acids are normal constituents of cell membranes, measurement of fatty acids composition and calculation of the ratio of polyunsaturated to saturated fatty acid components (PUFA/SFA) in red blood cell (RBC) membranes reflects the fatty acid content of the diet 15 and has been used as a reliable biomarker of fatty acid intake in epidemiological studies. 16 We have recently reported that the RBC membrane content of PUFA of the n-3 family (n-3 PUFA) affects the vascular response to vasodilators 17 and that a diet rich in PUFA that increases the n-3 PUFA content of RBC membrane decreases 24-hour blood pressure levels 18 and the carotid intima-media thickness in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%